PENGEMBANGAN KURIKULUM PAI BERBASIS KEILMUAN ISLAM TRADISONAL DI MA SMART ROUDLOTUL JINAN CILACAP - Mohamad Khoerul Anam; Suparjo (STKIP Subang, 2025)
This article discusses the development of the curriculum and evaluation of Islamic Religious Education (PAI) learning at MA Smart Roudlotul Jinan Cilacap. The focus of the study lies in the integration between the formal curriculum of the PAI group which includes the subjects of Akidah Akhlak, Fiqh, Al-Qur'an Hadith, and History of Islamic Culture with traditional Islamic science programs in the form of tahfidzul Qur'an and the study of yellow books, such as Fathul Qorib and Al-Miftah Sidogiri. This study uses a descriptive qualitative approach with data collection techniques in the form of literature studies, semi-structured interviews with teachers and ustadz, and participatory observation in learning activities. The results of the study show that MA Smart Roudlotul Jinan has implemented the Merdeka Curriculum with an integrative approach, namely combining national education values with the tradition of Islamic boarding school knowledge. The learning model used prioritizes active student participation, contextualization of Islamic values, and strengthening character through internalization of the morals and manners of students. Learning evaluation is carried out continuously through formative and summative assessments, as well as strengthening the Pancasila Student Profile. This integration shows that Islamic Religious Education in madrasas is able to answer the challenges of the times without abandoning the roots of classical Islamic traditions that have been deeply rooted in Indonesia.